VDC_100102372010.0X000001. Issue 1 (January 2018) - Marek, Ashley P.; Morancy, Jean Dominique; Chipman, Jeffrey G.; Nygaard, Rachel M.; Roach, Robert M.; Loor, Michele M.
The incidence of thoracolumbar spine fractures in blunt trauma is 4 to 5 per cent. These fractures may lead to neurologic injury, chronic back pain, and disability. Most studies from United States trauma centers focus on neurologic sequelae and/or compare treatment modalities. However, most patients with spine fractures do not have a neurologic deficit. Our primary objective was to determine the long-term outcome of traumatic thoracolumbar spine fractures, specifically addressing quality of life, chronic pain, and employment using a validated patient outcome survey. A chart review of 138 adult blunt trauma patients who sustained a thoracolumbar spine fracture and were admitted to our Level I trauma center from 2008 to 2013 was performed. A phone interview based on the Short-Form 12®, a general health survey, was then conducted. Of the 134 patients who met the inclusion criteria, 46 (34%) completed the survey. The average Short-Form 12® scores were 51.0 for the physical health component score and 52.9 for the mental health component score. These did not differ significantly from the national norm. Furthermore, 83 per cent (38) of the survey respondents returned to work full-time at the same level as before their injury. Majority of the patients (76%) said they did not have pain two to seven years after injury. Despite a commonly held belief that back injury leads to chronic pain and disability, after sustaining a thoracic or lumbar fracture, patients are generally able to return to work and have a comparable quality of life to the general population. This knowledge may be useful in counseling patients regarding expectations for recovery from trauma.